2009
DOI: 10.1007/s00540-009-0741-8
|View full text |Cite
|
Sign up to set email alerts
|

Does high-dose opioid anesthesia exacerbate ischemic spinal cord injury in rabbits?

Abstract: Our results suggest that neither i.v. fentanyl nor i.v. remifentanil added to 0.5 MAC isoflurane exacerbated ischemic spinal cord injury in rabbits when compared to 1 MAC isoflurane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Motor function was assessed using a method previously described with some modification (Drummond and Moore, 1989;Kakinohana et al, 2006;Shirasawa et al, 2009). A motor deficit index (MDI) graded as follows was used: 0, normal; 1, toes flat under the body when walking, but ataxia present; 2, knuckle walking; 3, movement of This article has not been copyedited and formatted.…”
Section: Assessment Of Motor Functionmentioning
confidence: 99%
“…Motor function was assessed using a method previously described with some modification (Drummond and Moore, 1989;Kakinohana et al, 2006;Shirasawa et al, 2009). A motor deficit index (MDI) graded as follows was used: 0, normal; 1, toes flat under the body when walking, but ataxia present; 2, knuckle walking; 3, movement of This article has not been copyedited and formatted.…”
Section: Assessment Of Motor Functionmentioning
confidence: 99%
“…The researchers demonstrated that high-dose fentanyl and remifentanil do not exacerbate ischaemic spinal cord injury. This may be a significant finding because many patients in ICU such as those in our study have sustained CNS damage [22]. …”
Section: Discussionmentioning
confidence: 95%
“…fentanyl nor i.v. remifentanil added to 0.5 MAC isoflurane exacerbated ischemic spinal cord injury in rabbits when compared to 1 MAC isoflurane [10]. In an experimental study, the authors determined whether morphine, administered via either the i.v.…”
Section: Opioids (Morphine Remifentanil and Fentanyl)mentioning
confidence: 99%